FUNGSIONALISASI BUDAYA LISAN NANDONG SMONG DI DESA SALUR KECAMATAN TEUPAH BARAT KABUPATEN SIMEULUE PROVINSI ACEH - Rahmadansyah, Risski; Juliani, Reni (Universitas Teuku Umar, 2023)
Nandong smongis an oral tradition in Simeulue Regency where in the past Nandong Smong was used as a means of saving from disasters, one of which was the tsunami disaster. The lyrics of nandong smong contain verses that have deep meaning for the community based on the experiences of the Simeulue people's ancestors. This experience can be passed on from one generation to the next. The purpose of this study is to reveal how nandong smong exists and becomes an art popular with the people of Simeulue, and how it is applied in everyday life. The theory used in this research is Malinowski's theory of functionalism. The approach used in this study is a qualitative approach. The studies found in this study, that this nandong smong was previously used as a means of rescue, poetry sung to relieve fatigue, and for lullaby. For nowadays nandon smong has become a form of local culture which is considered as art, education and a form of application of intracultural communication.